Additions to the rubiaceous flora of Papua New Guinea: Psychotria stolonifera and P-ternatifolia, two remarkable species from the Muller limestone - Takeuchi, W. (Phytotaxa, 2013)
Psychotria stolonifera and P. ternatifolia are newly described from limestone environments in the Muller Range of Papua New Guinea. Both species have unique vegetative characteristics allowing for instant separation from their closest allies. Psychotria stolonifera has an astonishing stoloniferous habit and diminutive stems; P. ternatifolia is the only Papuasian Psychotria with whorled leaves.